Women's Organizations During the National Movement - Situmeang, Talenta Febriani; Wardah, Wardah; Nst, Chindy Atika Wd (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This article discusses the role of women's organizations during the national movement. The role of Indonesian women in upholding the life of the nation cannot be ignored. Women's organizations were also born and participated in the struggle of the national movement. This research aims to determine the role of women in national movements and emerging organizations. This research uses qualitative analysis methods, specifically literature analysis. According to (Safitri & Anggraeni Dewi, 2021) this method is carried out by analyzing data from secondary sources of research articles related to the problems discussed in this research. The results of this research are an analysis of the roles and organizations of women that emerged during the national movemenKeyword : Health, Mental, Digital, Pancasila